An Application Of Infrared Sensors In Providing Instructions For Logic Gates In Automatic Doorstops - Lamsyah Abdil Hafiz; Zuraidah Tharo; Zulkarnain Lubis (Jurnal Scientia, 2024)
A parking space unit is an effective square measure for placing one vehicle (passenger car, bus/truck, or motorbike). This includes free space on the left and right of the vehicle meaning that the doors can be opened for passengers to get on and off as well as certain things such as space for special wheelchairs to park vehicles for people with disabilities as well as free space at the front and back. Parking Gate Bar, or by another name barriergate, is a device for restricting entry and exit of vehicles, the function of this parking door barrier or parking barrier is to indicate that a vehicle is allowed to enter or leave the parking lot, after passing through the parking guard post. Parking door barriers are usually operated using direct DC or AC electricity. , depending on needs and the price level which is adjusted to field conditions. The speed of the parking gate opening is one of the points that determines the price for the item, because the speed of opening will affect the overall parking service cycle, if the parking gate opens faster, more vehicles will be served. , whether leaving or entering the parking area, and ultimately parking customers will be more satisfied, if this speed reduces the waiting time of parking customers.